Nutritional status of iron, vitamin B12, folate, retinol and anemia in children 1 to 11 years old. Results of the Ensanut 2012 - Salvador Villalpando; Vanessa de la Cruz; Teresa Shamah-Levy; Rosario Rebollar; Alejandra Contreras-Manzano (Instituto Nacional de Salud Pública, 2015)
Objective. To describe the frequency of anemia, iron, vitamin B12, folate, retinol and predictors of anemia among Mexican children from Ensanut 2012. Materials and methods. Hemoglobin, ferritin, CRP, vitamin B12, retinol and folate concentrations were measured in 2 678 children aged 1-4 y and 4 275 children aged 5-11 y. Adjusted logistic regression models were constructed to assess the risk for anemia and micronutrient deficiencies. Results. In preschoolers and scholars, the overall prevalence of anemia was 20.4 and 9.7%, iron deficiency 14 and 9.3%, low vitamin B12 (LB12S) 1.9 and 2.6%; Folate 0.30 and 0%, and retinol depletion (VADp) 15.7 and 2.3%, respectively. ID and VADp were negatively associated with Hb (coefficient: -0.38 and -0.45, p<0.05); a higher log-CRP was associated with higher risk for anemia and VADp (OR=1.13 and OR=2.1, p<0.05, respectively). Conclusions. Iron deficiency, anemia and VADp are some of the main nutritional problems among Mexican infants